2013
DOI: 10.1007/s12011-013-9673-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Trace Elements on Longevity Population in China

Abstract: Based on background concentrations of elements in soils and the sixth population census data of China, this study discussed the distribution characteristics of soil elements and longevity population at province level in China. Percentages of the aging population are high in Southwest China and the eastern coastal region but low in western and northwestern regions. Provinces in South and Southwest China gain a high level of longevity, while the northern part of China has a low level of longevity. The background… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Thus, in a simple word, if we reveal prominently diminished serum (plasma) Gpx (Hpx) activity in adults, we can suggest the physiological senescence, age-associated diseases, accompanied by decrease of Gpx activity, and/or insufficient selenium consumption. Discussed facts, taken together, are in concordance with the data showing the positive correlation of selenium distribution with longevity [17]. Probably, the mechanisms supporting Gpx3 biosynthesis undergo involution in aging individuals earlier if the selenium consumption is regularly insufficient.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Thus, in a simple word, if we reveal prominently diminished serum (plasma) Gpx (Hpx) activity in adults, we can suggest the physiological senescence, age-associated diseases, accompanied by decrease of Gpx activity, and/or insufficient selenium consumption. Discussed facts, taken together, are in concordance with the data showing the positive correlation of selenium distribution with longevity [17]. Probably, the mechanisms supporting Gpx3 biosynthesis undergo involution in aging individuals earlier if the selenium consumption is regularly insufficient.…”
Section: Introductionsupporting
confidence: 80%
“…To maintain the Gpx3, the sufficient amount of the products, in which the selenium is commonly abundant and highly bioavailable (primarily wheat and meats, also fish, garlic, onions, broccoli, legumes, nuts, and several other productsreviewed in [20] and [21]), can be recommended to include in the diet. At the absence of selenium supplementations in these products, the geographical origin of them may be taken into account (some regions are selenium-deficient [17,21]). Direct consumption of nutritional supplements or 'nutraceuticals' based on selenium may also be effective.…”
Section: Introductionmentioning
confidence: 99%
“…The other 75 percent is determined by our lifestyles and the everyday choices we make (Buettner, 2010). Though controversial and complex, genetic factors (Schachter et al, 1994), climate (Lv et al, 2011a,b;Robine et al, 2012), natural environment (Liu et al, 2013;Magnolfi et al, 2009), socio-economic (Costa, 2005), and individual behaviors (Martin et al, 1996) have already been proven to influence lifespan, and thus influence the spatial distribution of longevity.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable climate provides abundant natural resources and suitable environment, which is beneficial for living healthier and longer. Former studies revealed that rich Selenium and Zinc in both natural environment and centenarians' body were largely found in China's "longevity villages", indicating those trace elements could influence the geographical aggregation distribution of the longevity, particularly for the centenarian proportion (Liu et al, 2013;Magnolfi et al, 2009;Savarino et al, 2000). Economic factors are also associated with longevity, through adequate food, balanced nutrition, good education, social security, and good access to healthcare, in addition to general satisfaction and happiness (Brown et al, 2012;Yi, D. Gu, & Land, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation